Effectiveness of cardiopulmonary bypass device educational program using painting and group discussion based on the Kirkpatrick model - Bahare Borusan; Mahla Salajegheh; Tania Dehesh (Zanjan University of Medical Sciences and Health Services, 2023)
Background & Objective: Clinical education has a very important contribution to the educational process of medical science students. Simple and understandable methods help to learn complex clinical processes, such as cardiopulmonary bypass device. The present study aimed to assess the effectiveness of the cardiopulmonary bypass device educational program using painting and group discussion for anesthesiology students based on the Kirkpatrick model. Materials & Methods: This quasi-experimental study was conducted on 30 undergraduate anesthesiology students. The intervention group (n=15) were trained on cardiopulmonary bypass device by painting and group discussion, and the control group (n=15) received common education. Pretest and posttest data were collected in the two studied groups using a researcher-made questionnaire to evaluate the reaction and learning. The data were analyzed in SPSS software. Results: At the reaction level, there was no statistically significant difference between the two groups. At the learning level, the mean score of knowledge in the intervention group changed significantly compared to the control group. Conclusion: As evidenced by the obtained results, the educational program of cardiopulmonary bypass device using painting and group discussion resulted in positive outcomes in the two evaluated levels of reaction and learning.